Work activity and phenylalanine levels in a population of young adults with classic PKU - Riva, Michele Augusto; Madotto, Fabiana; Turato, Massimo; Salvatici, Elisabetta; Indovina, Silvia; Giovannini, Marcello; Riva, Enrica; Cesana, Giancarlo (La Medicina del Lavoro, 2017)
Background: Phenylketonuria (PKU) is an inborn error of metabolism characterized by increased blood concentrations of phenylalanine (Phe). Objectives: The aim of the present study was to assess the association between the metabolic compliance of adult patients affected by classic PKU and the characteristics of their present and past occupations. Methods: The study population consisted of working adults, affected by classic PKU, and following a dietary treatment. Univariate linear-mixed models and multivariate analysis were applied to assess the association between Phe blood levels and individual covariates: age, sex, time at diagnosis, educational level and work characteristics. Results: A linear relationship was found with age (an average annual increase of 30.56 μMol/L (C.I. 95%: 7.53; 53.60) in the mean Phe blood levels). Full-time work appeared to be associated with a worse metabolic compliance when compared to part-time work (mean Phe blood levels >281.11 μMol/L). Shift work was related to a worse metabolic compliance, with mean Phe plasmatic levels >356.73 μMol/L. Conclusions: Our data suggests that work may influence the metabolic compliance in adults with PKU. In particular, a part-time employment could allow for a better metabolic compliance, while daily work should be preferred to shift work.